Thinking about mental health and spirituality from the Indigenous knowledge systems frame of reference - Lieketseng Ned; Lily Kpobi; Chioma Ohajunwa (Disability Studies Quarterly, 2022)
No abstract available.
Keywords: African Indigeneity; decolonization; Ghana; Indigenous knowledge; mental health; psychosocial disability; spirituality; South Africa